Answer:
r=63
Step-by-step explanation:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
r/3-(21)=0 r
Simplify —
3
r
— - 21 = 0
3 2.1 Subtracting a whole from a fraction
Rewrite the whole as a fraction using 3 as the denominator :
21 21 • 3
21 = —— = ——————
1 3
Equivalent fraction : The fraction thus generated looks different but has the same value as the whole
Common denominator : The equivalent fraction and the other fraction involved in the calculation share the same denominator
Answer:
See below
Step-by-step explanation:
4(x + 5) = 9x + 4x − 34
4x + 20 = 9x + 4x − 34 [Distributive]
4x + 20 = 13x − 34 {Combine Like Terms]
4x - 13x + 20 = 13x - 13x − 34 [Subtractive: -13x both sides]
-5x + 20 = - 34 [Combine Like Terms]
-5x + 20 - 20 = -34 - 20 [Subtractive: - 20 both sides]
-5x = -54 [Combine Like Terms]
x = -54/-5 [Division Property: divide both sides by -5]
x = - 10 4/5
Answer:
Im sorry im not sure how to do this either lol :/
Step-by-step explanation:
Answer:8 I think, sorry it it is wrong
Step-by-step explanation:
Answer:
b=3, y=6
Step-by-step explanation:
Label the 2 equations:
2b +6y= 42 -----(1)
2b +4y= 30 -----(2)
(1) -(2):
(2b +6y) -(2b +4y)= 42 -30
2b +6y -2b -4y= 12
2y= 12
y= 12 ÷2 <em>(</em><em>÷</em><em>2</em><em> </em><em>on</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
y= 6
Susbt. y=6 into (2):
2b +4(6)= 30
2b +24=30
2b= 30 -24 <em>(</em><em>-24</em><em> </em><em>on</em><em> </em><em>b</em><em>o</em><em>t</em><em>h</em><em> </em><em>sides</em><em>)</em>
2b= 6
b= 6 ÷2
b= 3